RELASI MATAHARI, BUMI DAN BULAN DALAM ILMU FALAK - Hudi Hudi (Isti`dal : Jurnal Studi Hukum Islam, 2014)
This paper discusses falak or astronomy that studies celestial objects, on the physical, motion, size and everything related to them. These three celestial objects are closely related to the calculation of the month and year, as well as the calculation of the new moon and eclipse which also affect the issue of Islamic law, particularly concerning the worship of prayer, fasting, charity, and pilgrimage. The main things that presented here are: (1) the Sun becomes the basis for determining the time-period in the earth's surface, namely the Gregorian calendar, qibla direction, time of prayer and the eclipse of the Sun; (2) Calculation of astronomy that deals with the earth is only limited to the issue of the direction of qibla. And the earth terms used in astronomy is latitude and longitude; and, (3) the Moon is used to determine the times associated with the Islamic calendar and lunar eclipses.astronomy, sun, earth, moon, Islamic lawTulisan ini mendiskusikan keilmuan falak atau astronomi yang mempelajari benda-benda langit, tentang fisiknya, geraknya, ukurannya dan segala yang berkaitan dengannya. Ketiga benda langit tersebut sangat berkaitan dengan perhitungan bulan dan tahun, serta perhitungan hilal dan gerhana yang juga turut serta memengaruhi persoalan hukum Islam, khususnya tentang peribadatan salat, puasa, zakat, dan haji. Hal utama yang disampaikan di sini adalah: (1) Matahari menjadi dasar dalam penentuan waktu-waktu di permukaan bumi, yaitu kalender Masehi, arah kiblat, waktu salat dan gerhana Matahari; (2) Penghitungan ilmu falak yang berkaitan dengan bumi hanya terbatas pada persoalan arah kiblat. Dan istilah bumi yang digunakan dalam ilmu falak adalah lintang tempat dan bujur tempat; dan,(3) Bulan dipergunakan untuk menentukan waktu-waktu yang berkaitan dengan kalender Hijriyah dan gerhana bulan.